SENTENCING OF PATHOLOGICAL GAMBLERS IN CANADA. LESSONS FOR SOUTH AFRICA? - Marita Carnelley (Obiter, 2023)
The focus of this note is on one specific type of sentencing, what is called “conditional sentence” in Canada, and “correctional supervision” in South Africa. The principles relating to this form of punishment in the two legal systems are again similar. It is a community-based punishment aimed at keeping the offender out of prison, and within society under strict conditions. The conditions in each case obviously depend on the circumstances of the case. In South Africa the measures mostly include house arrest, community service, monitoring and treatment. The choice of conditions in the Canadian legislation is wider, but includes a report to a supervisor, community service and attendance of a treatment programme (s 742.3 of the Canadian Criminal Code). The importance of this type of sentence for pathological gamblers is borne out by the fact that there is generally no need for these offenders to be removed from society. They are seldom violent, are susceptible to treatment outside the prison system and as such are capable of being rehabilitated. It is suggested that pathological gamblers in South Africa should, unless the seriousness of the crime demands otherwise, be sentenced to correctional supervision. This is the approach of the Canadian courts and should be the approach adopted by the South African courts.